МОДЕЛЮВАННЯ ІЄРАРХІЇ ЗАГРОЗ ЕФЕКТИВНОМУ РОЗВИТКУ СИСТЕМИ КОМЕРЦІЙНОГО СТРАХУВАННЯ - Позднякова, Людмила Олексіївна; Мамонова, Ганна Валеріївна (Науковий журнал «Світ фінансів», 2017)
Позднякова Л. О., Мамонова Г. В. Моделювання ієрархії загроз ефективному розвитку системи комерційного страхування. Розкрито сутність та введено у термінологічний обіг поняття “страхова система”, визначено її поелементне структурування. Виокремлено основні ендогенні та екзогенні загрози для ефективного розвитку системи комерційного страхування. Для систематизації виявлених загроз використано математичний метод моделювання, який дав змогу визначити ті загрози, які мають найсуттєвіший вплив на розвиток системи комерційного страхування. Надані практичні рекомендації щодо елімінації або палаталізації основних загроз для розвитку системи комерційного страхування. Позднякова Л. А., Мамонова А. В. Моделирование иерархии угроз эффективному развитию системы коммерческого страхования. Раскрыта сущность и введено в терминологический оборот понятие “страховая система”, определена ее поэлементная структура. Выделены основные эндогенные и экзогенные угрозы эффективному развитию системы коммерческого страхования. Для систематизации выявленных угроз использован метод моделирования, который позволил выделить те угрозы, которые имеют наиболее существенное влияние на развитие системы коммерческого страхования. Разработаны практические рекомендации элиминации или палатализации основных угроз для развития системы коммерческого страхования. Pozdniakova L., Mamonova A. Modeling hierarchy threats to effective development of commercial insurance. Introduction. The development of the national insurance system is accompanied by internal and external threats that require identification. Building a hierarchy of threats to the insurance system will develop a set of measures for their removal or mitigation.Purpose. The article is a hierarchy threats commercial insurance and the development of practical recommendations for their elimination or alleviation.Methods. Hierarchy threats to commercial insurance system built by the method of system analysis and graph theory.Results. Analysis and synthesis of scientific results to determine the nature and content of the insurance system, terminological allowed entering in turn improved the definition of the term. Thesis there is determined basic structural elements of the insurance system, namely commercial insurance system and social insurance system. Investigated and systematized the threat of development of commercial insurance. The model hierarchy threats of commercial insurance singled out the priorities for their elimination or mitigation by the method of system analysis and graph theory.Conclusions. Modeling hierarchy of threats to the system of commercial insurance led to the conclusion that the effective development of commercial insurance largely depends on the model of state regulation of the insurance market, its systematic and consistent reform.